THE 50th ANNIVERSARY OF THE AIRPORTS DEPARTMENT OF AIRPORTS FACULTY OF THE NATIONAL AVIATION UNIVERSITY (1969-2019) - Bieliatynskyi, Andrii; Pershakov, Valerii; Bileush, Anatolii; Pylypenko, Oleksandr (Proceedings of National Aviation University (archive), 2020)
The article is devoted to the history of 50 years of foundation of the airport department of the faculty of airports of National Aviation University (1969-2019). The information about the first deans of the Airports Faculty is represented. Since December 1969, the airports department under the leadership of its first head, Doctor of Technical Sciences, Professor V.I. Blochin has begun its work as profile and graduation department for the training of specialists in the specialty "Construction of aerodromes". Under his leadership, the first curriculum of the Airports Faculty and the curricula of special disciplines were developed, the team of teachers was formed, the first manuals were published and technical means of training were created. Within a short period of time the department created and equipped training laboratories for building materials, engineering networks of airfields, engineering geodesy and aerogeodesy, engineering geology, soil science and soil mechanics, the study of research and design of airports. Graduate designing at the department was based on the assignments of airlines. During 1972-1992, 786 diploma projects (including 138 foreign students) were defended, many of which were put into real airfields operation. The staff of the airport department is represented by photo of 1979 and nowadays the department having a new name of airports and highways reconstruction is represented by photo of 2010. During all its history the department was headed by: associate professor Belinsky I.O. (1979-1999), associate professor Talanov G.P. (1999-2000), associate professor Shinkarchuk M.V. (2000-2001), professor Veryuzhsky Yu.V. (2001-2002), professor Tsikhanovsky V.K. (2002-2008), professor Bieliatynskyi A.O. (from 2008 to present day). Scientific and teaching activities at the department are performed by highly qualified teachers: 4 professors and 7 associate professors. The teachers of the department are the authors of many textbooks, manuals, monographs and normative documents on design as well as the operation of highways and airfields. In addition, the department cooperates closely with various educational, research, design, civil engineering and airlines enterprises of Ukraine and abroad: UkrNDIProektStalonstruktsiya, Ukravtodor, Boryspil and Kyiv International Airports, as well as universities of Lithuania, Latvia and Germany. NAU graduates work at airlines in Ukraine and numerous countries in Europe, Asia, Africa and America.